Comecon and the Failure of Eastern Bloc Regional Integration - Christie, Micah; Garlick, Jeremy; Shakhanova, Gaziza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
An examination of the failure of Comecon using Fred Halliday's concept of internationalism as being both an cluster of ideas and politics that reflect those ideas. This thesis compares both the EC and Comecon and finds that the internationalist ideas in the EC were shared more by these members and that they were reflected in the structures and actions of the EC. In Comecon, the Marxist ideas of internationalism were eventually not reflected in the politics or structures of Comecon. The failure to align the shifting ideas of internationalism, this thesis argues, will contribute to a failure of integration and the international organization.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses